Epigenetic changes in shear-stressed endothelial cells - Pinto, Thaís Silva [UNESP] (2024)
Epigenetic changes, particularly histone compaction modifications, have emerged as critical regulators in the epigenetic pathway driving endothelial cell phenotype under constant exposure to laminar forces induced by blood flow. However, the underlying epigenetic mechanisms governing endothelial cell behavior in this context remain poorly understood. To address this knowledge gap, we conducted in vitro experiments using human umbilical vein endothelial cells subjected to various tensional forces simulating pathophysiological blood flow shear stress conditions, ranging from normotensive to hypertensive forces. Our study uncovers a noteworthy observation wherein endothelial cells exposed to high shear stress demonstrate a decrease in the epigenetic marks H3K4ac and H3K27ac, accompanied by significant alterations in the levels of HDAC (histone deacetylase) proteins. Moreover, we demonstrate a negative regulatory effect of increased shear stress on HOXA13 gene expression and a concomitant increase in the expression of the long noncoding RNA, HOTTIP, suggesting a direct association with the suppression of HOXA13. Collectively, these findings represent the first evidence of the role of histone-related epigenetic modifications in modulating chromatin compaction during mechanosignaling of endothelial cells in response to elevated shear stress forces. Additionally, our results highlight the importance of understanding the physiological role of HOXA13 in vascular biology and hypertensive patients, emphasizing the potential for developing small molecules to modulate its activity. These findings warrant further preclinical investigations and open new avenues for therapeutic interventions targeting epigenetic mechanisms in hypertensive conditions.